Mathematical models for data processing in information systems - Linkeová, Ivana (Univerzita Pardubice, 2009)
Frequent requirement in processing the data from information systems is to find the appropriate analytical expression for the relation among variables or quantities and the possibility of accurate graphical representation of this expression. This paper is focused on the standard and non-standard tools in Microsoft Excel by means of which it is possible to achieve these requirements.
Keywords: Information Systems; data processing; trend lines; regression curves; interpolation curve